Diagnostic utility of clinical and epidemiologic features in fever of unknown origin - Campañá, Victor Roca; Paneque, Rosa Eugenia Jiménez; Silva, Héctor Manuel Rodríguez (The European Research Journal, 2019)
Objectives: To assess the diagnostic utility of clinical features in the major diagnostic categories of Fever of unknown origin (FUO).Methods: One hundred and thirty-three patients meeting the classic criteria of FUO were included in the study. A structured diagnostic protocol was used in all cases. Sensitivity, specificity, positive and negative predictive values (PPV and NPVs), and likelihood ratios of positive and negative tests (LR+ and LR-) were estimated with 95% confidence intervals (95% CIs) for all clinical findings.Results: Clinical and epidemiologic features with best diagnostic utility indexes for the three major diagnostic categories were: weight loss of 15 pounds or more (sensitivity, 68.4%, 95% CI: 52.33-84.52), pallor of the skin and mucous membranes (sensitivity, 65.7%, 95% CI: 49.39-82.19), prior medical history of cancer (PPV, 63.6%, 95% CI: 30.66-96.61; LR+, 4.38, 95% CI: 1.36-14.09), lymphadenopathy (LR+, 2.2, 95% CI: 1.11-4.74), for neoplasms; arthritis (PPV, 72%, 95% CI: 51.84-93.61), prior family history of collagen diseases (PPV, 100%, 95% CI: 91.67-100.00), neurologic disorder (LR+, 5.1, 95% CI: 1.37-19.68), myalgia (LR+, 4.1, 95% CI: 1.45-11.88) and skin lesions (LR+, 3.0, 95% CI: 1.51-6.22) for noninfectious inflammatory diseases;  weight loss of 15 pounds or more (sensitivity, 50%, 95% CI: 27.91-72.09), epidemiological history of previous tuberculosis or tuberculosis exposure (LR+, 9.0, 95% CI: 1.76-46.77), and jaundice (LR+, 2.73, 95% CI: 0.7-10.63) for infections. Conclusions: We identified clinical data emerging from the anamnesis and physical examination that may help to guide the diagnostic process in FUO.